PENCABUTAN HAK POLITIK MEMILIH DAN DIPILIH DALAM PEMBAHARUAN HUKUM PIDANA - Kabes, Irianto; Gultom, Elfrida Ratnawati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
In the 2024 General Election, it was recorded that there were 27 (twenty seven) legislative candidates (candidates) who had been convicted in corruption cases running again in the 2024 General Election through 8 (eight) Political Parties, even based on the results of the legislative General Election (Pileg) there is the name of one of the convicts in a corruption case who won the most votes in his electoral district and will therefore be appointed as a Member of the Legislative Assembly in 2024. This research aims to examine this problem in more detail. Regarding the length of time for revocation of rights, which in previous regulations was not regulated in corruption regulations but rather through the decision of the constitutional guard agency in 2019, the author will analyze through legal reforms that have been passed in 2023. The research was carried out normatively and is descriptive in nature. By using secondary data to analyze qualitatively, and drawing conclusions using deductive logic. The results of research on criminal law reform have explicitly determined the length of revocation of political rights which must be set at a minimum of two years and a maximum of five years. The author provides suggestions for criminal law reform, regarding the revocation of political rights in terms of voting, minimum and maximum time limits can be set, however the revocation of the right to vote can be carried out forever according to the constitution and law.Keywords: Criminal Law Reform, Additional Crimes, Revocation of Political Rights